1990
DOI: 10.1210/jcem-71-5-1330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Insulin-Like Growth Factor-Binding Protein-3 (IGFBP-3) and IGFBP-2 in Human Follicular Fluid*

Abstract: Two major insulin-like growth factor-binding proteins, IGFBP-2 and IGFBP-3, were identified by Western ligand blotting of human follicular fluid (FF) aspirated from luteinizing follicles during ovarian stimulation with human menopausal gonadotropin (LH and FSH). IGFBP-1 was also present in FF, and an IGFBP with a mol wt of 24000 daltons, present in serum, appeared to be absent in FF. Identification of IGFBP-1, IGFBP-2, and IGFBP-3 was confirmed using IGFBP-specific antisera. IGF-I and IGF-II levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 68 publications
3
21
1
Order By: Relevance
“…Human follicular fluid contains immunoreactive IGFBP-1 [26,27] and cultured human luteinizing granu losa cells synthesize IGFBP-1 [29,30]. Western immunoblotting in this study further suggests IGFBP-1 produc tion by human luteinizinggranulosa cells.…”
Section: Igf-i (Log M)supporting
confidence: 59%
See 1 more Smart Citation
“…Human follicular fluid contains immunoreactive IGFBP-1 [26,27] and cultured human luteinizing granu losa cells synthesize IGFBP-1 [29,30]. Western immunoblotting in this study further suggests IGFBP-1 produc tion by human luteinizinggranulosa cells.…”
Section: Igf-i (Log M)supporting
confidence: 59%
“…In humans, luteinizing granulosa cells were found to contain mRNAs encoding IGFBP-1, -2, -3, and -4 [24,25], and these four IGFBPs have been demonstrated in follicular fluid both from hyperstimulated ovarian cycles and from spontaneous cycles [26][27][28], Cultured luteiniz ing granulosa cells synthesize IGFBP-1 [29] that is con trolled by both adenylate-cyclase-and protein-kinase-Cdependent pathways [30]. IGFBP-1 inhibits IGF-I-mediated DNA amplification in human luteinizing granulo sa cells [31].…”
Section: Introductionmentioning
confidence: 99%
“…Giudice et al [24] observed decreased amounts of IGFBPs in immature FFs by Western ligand blotting analysis compared with that in mature FFs. Chang et al [25] reported that the fertilization rate was elevated with a high IGFBP-1 concentration in FFs.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, insulin excess may up-regulate hepatic production of GHBP [54]. This potential link between insulin and functional activity of the somatotropic axis is further supported by the ability of insulin excess to inhibit hepatic production of IGFBP-1, with the marked suppression of IGFBP-1 levels in obese PCOS resulting in a more than 10-fold increase in the IGF-I/IGFBP-1 ratio The follicular fluid of human ovaries has been shown to contain multiple species of IGFBPs which are thought to regulate the bioavailability of the IGFs to their target tissues [55][56][57] . There are discrete changes in IGFBP concentrations in follicular fluids which are correlated with the physiological state of the follicle [58,59].…”
Section: Somatotropic Axis In Pcosmentioning
confidence: 99%